Pola Komunikasi Kepala Desa Petak Dalam Pengelolaan Progam Inovasi Desa Petak Menuju Pemberdayaan Masyarakat - Ramadhani Praptama; Alfin Fatikh (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2022)
The aim of the study was to find out the communication pattern of the innovation program by the village head. This type of qualitative research with a descriptive approach, data collection techniques with observation, interviews, and documentation. Data analysis technique with data reduction, data display and conclusion. The results of the study show: 1) Orientation Phase, the village head introduces the village innovation program plan. 2) Explorative Affective Exchange Stage, the development of interpersonal relationships marked by agreement and understanding. 3) Affective Exchange Stage, the emergence of critical and evaluative feelings at a deeper level. 4) Stable Exchange Stage, each individual is enabled to estimate their respective actions and respond accordingly. Petak Village Head Communication Patterns are 1) Chain Communication Patterns; the village head provides direction and stimulus to the community with the Kadus as an intermediary for information. 2) Circular Communication Patterns; communication in which the communicator provides a source of reciprocal response to other communicators.